Bible Odyssey: people, places and passages (The Society of Biblical Literature, 2017)
"Explore the fascinating origins of the Bible and its eventful history. On Bible Odyssey, the world’s leading scholars share the latest historical and literary research on key people, places, and passages of the Bible"